2016
DOI: 10.1111/jnc.13558
|View full text |Cite
|
Sign up to set email alerts
|

Smad3 deficiency inhibits dentate gyrus LTP by enhancing GABAA neurotransmission

Abstract: Transforming growth factor-b signaling through intracellular Smad3 has been implicated in Parkinson's disease (PD) and it fulfills an important role in the neurogenesis and synaptic plasticity that occurs in the adult dentate gyrus (DG). The longterm potentiation (LTP) induced in the DG by high-frequency stimulation of the medial perforant pathway is abolished in the DG of Smad3-deficient mice, but not in the CA1 hippocampal region. Here, we show that NMDA-and AMPA-type glutamate receptors do not participate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 61 publications
4
19
0
Order By: Relevance
“…Moreover, these findings parallel the upregulation of VEGF in the lesioned striatum of PD rats that received intermittent SCS (1 h/day for 7 consecutive days) (Shinko et al, 2014). That SCS modulates specific vasculature-associated growth factors suggests a crosstalk between electrical stimulation and growth factor secretion (Bagetta et al, 2011;Escamilla-Sevilla et al, 2011;Seifried et al, 2013;Maioli et al, 2015;Muñoz et al, 2016), which may mediate the observed increase in laminin-positive vascular area in the cerebral cortex of SCS-treated PD rats.…”
Section: Enhanced Angiogenesis By Scssupporting
confidence: 60%
“…Moreover, these findings parallel the upregulation of VEGF in the lesioned striatum of PD rats that received intermittent SCS (1 h/day for 7 consecutive days) (Shinko et al, 2014). That SCS modulates specific vasculature-associated growth factors suggests a crosstalk between electrical stimulation and growth factor secretion (Bagetta et al, 2011;Escamilla-Sevilla et al, 2011;Seifried et al, 2013;Maioli et al, 2015;Muñoz et al, 2016), which may mediate the observed increase in laminin-positive vascular area in the cerebral cortex of SCS-treated PD rats.…”
Section: Enhanced Angiogenesis By Scssupporting
confidence: 60%
“…High doses of the AChEI, i.e., donepezil, were licensed in the USA for moderate-severe AD, and the association AChEI with memantine was proposed for AD at this stage. Molino et al [131] reviewed different clinical trials regarding effectiveness of memantine, donepezil, or the two drugs in combination to manage moderate-severe AD. The authors considered double-blind, placebo-controlled, randomized trials, employing memantine, donepezil independently or in conjunction with memantine and compared to placebo treatments in moderately severe AD.…”
Section: Neurotransmitter-based Therapeutics In Admentioning
confidence: 99%
“…These results indicated selective inhibition of astrocytic GABA synthesis or release and may be useful for improving memory in AD [130]. In Parkinson’s disease, Smad3 deficiency as noted in GABA (A) neurotransmission was observed to increase through the inhibition of dentate gyrus LTP [131]. Similarly, alteration of GABA neurotransmission is thought to produce hippocampal cognitive dysfunction in Down’s syndrome patients with AD.…”
Section: Neurotransmitter-based Therapeutics In Admentioning
confidence: 99%
“…A recent study by Muñoz et al showed a new mouse model of Parkinson’s disease that could also be rescued by targeting GABA A receptors. Smad3 deficient mice fail to induce LTP in the dentate gyrus due to enhanced GABA A receptor-mediated activity, in addition to decreased adult neurogenesis and dysregulated hippocampal function (Muñoz et al, 2016). Picrotoxin, a GABA A antagonist, rescued this phenotype.…”
Section: Gaba Regulation Of Adult Hippocampal Neurogenesis As a Potenmentioning
confidence: 99%